A Study on Postnatal Depression among Women Attending Tertiary Care Hospital in Davanagere, Karnataka - Sandhya Rani Javalkar; Vanitha S S (Medsci Publications, 2018)
Introduction: Postnatal depression (PND) is a public health problem as it arises as a common complication of childbearing and it significantly affects women and their families Objectives: To determine the prevalence of postnatal depression among women attending a Tertiary Care Hospital in Davangere and identify the risk factors determining postnatal depression. Methodology: A cross sectional study conducted in a Tertiary Care Hospital in Davangere district, Karnataka among 151 women in postnatal period. The Edinburgh Postnatal Depression Scale (EPDS) is used as screening tool identifying patients at risk for postnatal depression. Data is collected by interview method and analyzed using SPSS. Results: This study revealed postnatal depression to be 23(15.2%) among the study participants according to EPDS score >10. Statistical Analysis revealed significant association of socio demographic factors like type of family, obstetric factors like mode of delivery, type of delivery, complications in pregnancy and other factors like Low mood during pregnancy. Conclusion This study we found the prevalence of post partum depression to be 15.2%. Development of a routine screening program to screen all post natal women using a validated screening tool can be really helpful in timely interventions when needed.